STUDY OF TREATMENT OUTCOME OF NEW SPUTUM SMEAR POSITIVE TB CASES UNDER DOTS – STRATEGY - DR. SULTAN RIZWAN AHMAD; DR. G. D. VELHAL (International Journal of Pharma and Bio Sciences, 2013)
Background: In India every year, 1.8 million new cases of TB occur, of which about 0.8 million are sputum positive pulmonary TB cases. This study attempts to find out the treatment outcomes of smear positive cases and factors that affect the outcome. Methodology: Community based prospective observational study was conducted in urban slums of Mumbai. Total 281 newly diagnosed sputum smear positive TB cases were selected, followed-up, and treatment outcome was obtained within 1 month after completion of continuous phase of treatment. Results: Tuberculosis is common among the illiterates (nearly 60 %) and labourers (53%), people below poverty line (90%), living in overcrowded houses (75%). In the present study, 42.7% were cured, 24.56% were treatment completed, 8.19% had died, and 4.98% were failure and 19.57% were defaulters after treatment. The cure rates and treatment completion were comparatively better in the age groups of 0-49 years (44.50 & 26.7%) and among females (53.85% &32.31%). Defaulter, Death and failure are more in labourer (22.78%, 9.49 %& 7.59%) and illiterates (26.79%, 10.71% & 6.55%). Cure rates and treatment completion are low among smokers (39.1% & 21.85%) and tobacco chewer (29.73% & 16.22%). Conclusion: Lower cure rates and high defaulters are found to be associated with illiteracy and smoking, which can be modified by IEC and focus service delivery on high risk groups.